Advances in microbial sulfoquinovose catabolism - Chen, Yiwei; Liu, Dazhi; Chu, Ruoxing; Li, Zongyuan; Zhang, Yueya; Ma, Kailiang; Jiang, Li; Yang, Qiaoyu; Lu, Fengxia; Zhang, Yan; Tong, Yang (Frontiers in Microbiology, 2026)
Sulfoquinovose (SQ) serves as the polar head group of sulfolipids in photosynthetic organisms. Given the substantial biomass of these organisms, the estimated global annual production of SQ is around 10 billion tons, making it one of the most abundant sulfur-containing organic compounds in nature. The microbial degradation of SQ constitutes a critical component of the global sulfur cycle and is increasingly recognized for its relevance to human health, particularly through its metabolism by the gut bacteria. Microorganisms employ two principal classes of catabolic pathways to degrade SQ: (i) C-S bond cleavage pathways, including the sulfo-ASMO (alkanesulfonate monooxygenase-dependent) and sulfo-ASDO (alkanesulfonate dioxygenase-dependent) pathways, which release glucose and sulfite; and (ii) C-C bond cleavage pathways, including sulfo-EMP (sulfoglycolytic Embden-Meyerhof-Parnas), sulfo-ED (sulfoglycolytic Entner-Doudoroff), sulfo-TAL (sulfoglycolytic transaldolase), and sulfo-TK (sulfoglycolytic transketolase) pathways, which yield short-chain sulfonates such as sulfolactate (SL) and dihydroxypropanesulfonate (DHPS). These sulfonated intermediates can undergo further degradation, releasing sulfite and short chain carbohydrates. Sulfite-reducing Bilophila wadsworthia utilizes them to generate respiratory terminal electron acceptor forming H₂S, which is toxic and a potential cause of inflammation and colon cancer. Here we systematically review the SQ catabolic pathways and the degradation mechanisms of the sulfonated intermediates. In addition, the significant implications of SQ degradation in human gut are discussed briefly.